كفاح عبد الرضا عليوي (Journal of the College of Basic Education, 2025)
The subject of moral values ​​is one of the basic fields in education and the rest of the behavioral sciences. The Book of God, in its stories, used various paths to guide people and address them, ranging between severity and softness, and between encouragement and intimidation. The path of guidance was one of the most important paths of conveyance in the Qur’anic stories. By presenting the stories of the prophets, messengers, and the righteous, these stories included moral values ​​aimed at the well-being of the individual and society. The interest of educational scholars in the subject of values ​​is due to the fact that these values ​​are directly related to the goals that education seeks to achieve, and the Holy Qur’an is the most important source of those values, which requires a return to it, and with Quranic educational studies are diverse, but they lack linking them to what the individual needs The importance of this study lies in that it works to employ the moral values ​​inferred from Qur’anic stories and put them in a proposed concept for teaching them within the framework of the Islamic education curriculum, which increases the return, usefulness, and scientific feasibility of this study.This study included four requirements. The first requirement included the concept of moral value and how to derive it from Qur’anic stories, while the second requirement included the concept of the Qur’anic story, tracing its origins, and presenting the events of nations and peoples. As well as the news of the prophets and messengers, which achieves its goal of clarifying the message of Islam. As for the third requirement, its title was the moral values ​​in the Qur’anic story and their impact on society, as it contained the importance of the moral values ​​of the Qur’anic stories through the story of the Prophet Moses, peace be upon him, and the story of Luqman the Wise, and what they included. These two stories are about moral values ​​such as patience and honoring one’s parents, the value of giving thanks to God and forbidding associating others with Him, enjoining good and forbidding evil...etc.Then came the fourth and final requirement, which included the results, the most important of which were:1.The most important source of sublime moral values ​​is the Holy Qur’an in general and Quranic stories in particular.The field of Qur’anic stories is a fertile field and a wide area for study and research on everything that concerns the life of the individual and his social and moral fabric. Then the recommendations, the most important of which were:that it. Contemporary education must start from the Islamic faith and its moral values.Highlighting the moral values ​​in Quranic stories in the form of small booklets or publications that suit the nature of children, and placing them in the school library to contribute to their development. Then came the sources adopted by the study, and finally a summary of the research in English